Pengeluaran R&D Dan Financial Sustainability Serta Peran Marketing Performance, Gross Margin, Dan Technological Performance Sebagai Variabel Mediasi - Wardana, Ditya (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
This research intend to analyze the influence of R&D expenditure to financial sustainability with marketing performance, gross margin, and technological performance as mediating variable. The analysis technique used is PLS (Partial Least Square). The research population was the manufacture industry registered in Indonesia Stock Exchange in 2007-2016. The number of sampleswas 130 samples from 13 companies for approximately 10 years running. The samples were selected using purposive sampling technique. Results of hypothesis testing showed that high R&D expenditure had no impact on the high ability of the company to reach financial sustainability. This research also shows that R & D activity has been able to improve marketing performance by creating high quality products and products that provide economic, social, and environmental benefits so that the company can achieve financial sustainbaility.